Light-Dark Cycle Disruption in Hypothalamus Tissue of Mus Musculus Causes Change in the Expression of Gm45928 Gene - Amaan Aftab Farooqui; Hitesh Kumar Bhattarai; Akio Ghimire; Rabin Pokhrel; Puspa Chimauriya (International Journal of Cell Biology and Cellular Functions, 2025)
The majority of organisms on earth display consistent 24-hour rhythms in their physiology and behavior due to circadian biology. Light and dark cycles play a key role in setting our internal body clock, which controls things like our sleep patterns, hormone levels, body temperature, and metabolism. The disruption of the light-dark cycle has significant effects on the molecular and behavioral rhythms of the circadian clock of hypothalamus. Gm45928 is a locus that represents naturally occurring read through transcription between the neighboring Clcf1 and Pold4 genes on chromosome 19. We employed transcriptomic analysis to investigate the gene expression patterns in hypothalamus tissues of M. musculus in varying light-dark conditions and different diet, antibiotic treatment conditions. To perform the analysis, we utilized the R Studio software, which provided us with a comprehensive set of tools and packages, enabling us to process and analyze the transcriptomic data efficiently. Comparing between the two treated groups, CD and ABX, reveals significantly higher gene expression, suggesting a potential protective effect of ABX treatment against gut microbes compared to the CD group.
Keywords: Immune cell; cellular function; circadian rhythm; differential gene expression; fold change; hypothalamus tissue; metadata; normalization